PELATIHAN PEMASARAN DARING PADA UMKM CV BINTANG FOOD BANTUL YOGYAKARTA - Fikri Farhan Fikri Farhan; Zidni Husnia Fachrunnisa (Randang Tana - Jurnal Pengabdian Masyarakat, 2022)
The COVID-19 pandemic that has spread globally since early 2020 has had an impact on various aspects, including the business aspect. Business people are forced to face the various changes that occur due to the pandemic. The pandemic is changing consumer behavior adapting to online shopping. As such, it is regarded as something normal. Therefore, business people who want to survive in the midst of the crisis due to COVID-19 must adapt to changes in consumer behavior, which now tends to always shop online. CV Bintang Food is one of the MSMEs affected by covid 19. The pandemic has caused a decrease in consumer demand for products which also resulted in income decrease. Therefore, this community service activity aims to help CV Bintang Food adapt to the changes that occur due to the pandemic. The method used is by observing and providing training related to promotion and sales through online media (Whatsapp, Facebook, and Instagram). This community service activity is carried out in three stages, namely: preparation, implementation, and evaluation stages. It is hoped that after this service, CV Bintang Food is able to practice selling their products through online media which will then lead to an increase in their sales